Desarrollo de un sistema informático aplicando SCRUM para mejorar la gestión académica del Instituto Manuel Banda de Guadalupe – La Libertad - Garro Portales, Harry Miguel (2016)
This document describes the development of a computer system called "SGA" version 1.0, which will improve the Academic Management Institute Manuel Banda off Guadalupe - Liberty._x000D_ The Institute Manuel Banda of Guadalupe has been experiencing an increase in their freshmen, which has meant an increase of students. Because all its activities the Institute is done manually and does not have a computer system to help improve the automation of the academic, this entails performing repetitive tasks, have inconsistent records also waste time students to manually perform the entire registration process, causing discomfort. So the development of a software-type computer system which would give good service is proposed that online enrollment dare make a website more quickly, efficiently and safely._x000D_ To develop the computer system had to learn dare surveys and meetings with members of the aforementioned Institute, the SCRUM methodology was used. Was used the PHP programming language and HTML, also the Netbeans IDE 8.02 previously set for the creation of the system